Collaborative ties and ambidextrous innovation: insights from internal and external knowledge acquisition. Issue 3 (15th March 2020) - Xie, Xuemei; Gao, Yanru; Zang, Zhipeng; Meng, Xiaohua
ABSTRACT: Building collaborative ties has become an increasingly important strategy for influencing firms' ambidextrous innovation in transition economies, we examine the relationship between collaborative ties and ambidextrous innovation—with a focus on the mediating effect of knowledge acquisition using firm-level data in China. The empirical results reveal several important findings. First, collaborative ties among partners have a positive effect on firms' ambidextrous innovation. Second, collaborative ties among partners are more beneficial to the firm's external knowledge acquisition than internal knowledge acquisition. Lastly, the mediating effect of internal knowledge acquisition on the relationship between collaborative ties and ambidextrous innovation of firms is higher than that of external knowledge acquisition. These findings contribute to the literature on ambidexterity theory. Moreover, these findings also extend our understanding of the importance of the integration of internal and external knowledge acquisition in collaborative relationships, and enrich knowledge management literature within the collaborative ties framework.